Efficacy and Safety of Bojungikgi-Tang for Persistent Allergic Rhinitis: A Study Protocol for a Randomized, Double-Blind, Placebo-Controlled, Phase II Trial. (20th June 2022) - Lee, Su Won; Choi, Jin Kwan; Lyu, Yee Ran; Yang, Won Kyung; Kim, Seung Hyung; Kim, Je Hyun; Kim, Si Yeon; Kang, Weechang; Jung, In Chul; Lee, Beom Joon; Choi, Jun Yong; Kim, Taesoo; et al.
Abstract : Background . Allergic rhinitis (AR) is a common disease, and conventional medications are often insufficient for treatment. Bojungikgi-tang (BJIGT) is an herbal medicine widely used in traditional medicine and has anti-inflammatory and immunoregulatory effects. We hypothesize that BJIGT would improve nasal symptoms in patients with persistent AR (PAR). Methods . This is a randomized, double-blind, placebo-controlled, phase II trial. A total of 105 patients, identified with perennial allergens, with a history of PAR and a mean total nasal symptom score (TNSS) ≥ 5 during the run-in period will be recruited from Daejeon Korean Medicine Hospital. Participants will be randomly assigned to a high-dose BJIGT group, standard-dose BJIGT group, or control group (placebo) in a 1 : 1 : 1 allocation ratio after a week run-in period. The treatment medication will be taken three times per day for 4 weeks. The primary outcome measure is the mean change in the TNSS before and after medication. The secondary outcome measures include the Korean Allergic Rhinitis-Specific Quality of Life Questionnaire, total IgE and eosinophil count, overall assessment of AR, pattern identification questionnaire for AR, and Sasang constitution. Discussion . The aim of this study is to investigate the efficacy and safety of BJIGT in the treatment of PAR and to determine the suitable dosage of BJIGT. Therefore, we planned a randomized, controlled, phase II trial of two different doses of BJIGT compared with placebo, and the results of this study are expected to provide evidence for the use of BJIGT as a treatment of PAR. Trial Registration. The National Clinical Trial Registry Clinical Research Information Service, CRIS, KCT0006616, https://cris.nih.go.kr/cris/search/detailSearch.do/20706.